Nandi facing the sanctum - Temples of India Project Team (Jio Institute, 2024)
A black stone figure of nandi is placed on one of the broad stairs leading to the garbhagriha. The nandi is shown seated on a raised platform, facing the sanctum where a Shiva Linga is placed at the center of the sanctum. The nandi sculpture has well-defined horns and hump, and it is adorned with a neck belt of bells. On his back, an ornately carved saddle can also be seen.